Lingual characteristics of blog commentaries (а study of tнe content of «українська правда» (‘ukrainian truth’) website) - Andreyeva, Tetyana; Andreyeva, T. M.; Андрєєва Тетяна Михайлівна (Одеса, 2018)
У середовищі Інтернет-комунікації коментування має значне поширення. Опція «коментування» активована щодо абсолютної більшості сучасних Інтернет-ресурсів. Найперше, що впадає в око після ознайомлення з текстами коментарів до блогів на «Українській правді», так це «українсько-російська макаронічність»-мішанина лексичних компонентів російської та української мов. Значною мірою це відбувається з метою пародіювання та залучення до тексту номінацій, що позначають розтиражовані пропагандою ідеологеми, ставлення до яких теж здебільшого несерйозне. Цілком природним явищем у текстах коментарів є неологізми/оказіоналізми. Тут вони можуть творитися без будь-яких обмежень щодо форми та змісту. Доволі поширеним у текстах коментарів є перифразування. Виявлено випадки, коли коментатори вставляють у слова небуквені графічні засоби. Таке незвичне оформлення слова здійснює акцентування уваги на ньому. У текстах коментарів виявлена так звана «капслокізація». За її допомогою автор прагне виділити відповідний компонент, підкреслити його, надати більшої ваги. Інтертекстуальність аналізованим коментарям забезпечують цитування та алюзії. Непоодинокі випадки вживання фразеологізмів. Можлива фразеологічна трансформація. Для втілення відповідних інтенцій коментатори зумисно деформують слова. Щоб не перейти межу, зберегти реноме, проте використати потрібне слово, автори коментарів здійснюють графічне маскування обсценної та лайливої лексики. Водночас виявлено багато помилок та відхилень від загальноприйнятих правил писемного мовлення. Отже, віртуальна мовна особистість, - учасник Мережевої комунікації, - використовуючи проаналізовані мовні засоби, демонструє креативність у їхньому виборі та використанні.

The paper focuses on the lingual features of blogs, viewed as a new form of communication that emerged due to the Internet and is subdivided into two genre groups of texts: a post (a prepared and edited message of its author) and commentaries (spontaneous short messages, posted by the post readers, that reflect the oral speech). The research is based on the commentaries of “Ukrainian Truth" («Українськa правдa») blogs, whose lexico-grammatical content is termed as "Ukrainian-Russian Macaroni", i.e. a mix- ture of lexical components of both Russian and Ukrainian. lt is found out that in the majority of cases Ukrainian texts have transliterated components of the Russian language which occur with the purpose of parodying or denoting the ideas implemented by propaganda. At the same time, it is not typical of Ukrainian language units to squeeze into Russian texts. Neologisms and ad- hoc formations, being created without any restrictions as to the form and content, are natural for blog commentaries. Along with neologisms represented by single lexemes blog commentaries are characterised by newly-coined phraseological units, idioms and paraphrasing. There are cases when commentators insert non-lingual graphical means into words to focus the readers' attention on diferent connotative meanings. By using capital letters only, the author seeks to highlight a certain component of the text, thus emphasizing it. Some commentaries contain, along with the letters, graphical mathematical symbols. lntertextuality of the analyzed commentaries is achieved by using quotations and allusions. ln order to fulfil the corresponding intentions, the commentators may deliberately distort the words as well as there may be some errors and deviations from the generally accepted rules of written speech. The study of lingual specificity of lnternet communication presents a significant scientific perspective, since the field of network communication shows its constant growth, attracting more and more users.
Andreyeva, Tetyana. Lingual characteristics of blog commentaries (а study of tнe content of «українська правда» (‘ukrainian truth’) website) / T. Andreyeva // Одеський лінгвістичний вісник. – 2018. – Вип. 11. – С. 112-117. DOI https://doi.org/10.32837/2312-3192-2018-11-112-118
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Графічні засоби; Інтернет-комунікація; коментар; інтерактивність; компонент; текст; Graphical means; Internet communication; commentary; interactivity; component; text